2009
DOI: 10.1111/j.1365-2966.2009.14596.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent torque reversal of 4U 1907+09

Abstract: We present timing and spectral analysis of RXTE‐PCA (Proportional Counter Array) observations of the accretion powered pulsar 4U 1907+09 between 2007 June and 2008 August. 4U 1907+09 had been in a spin‐down episode with a spin‐down rate of −3.54 × 10−14 Hz s−1 before 1999. From RXTE observations after 2001 March, the source showed a ∼60 per cent decrease in spin‐down magnitude, and INTEGRAL observations after 2003 March showed that source started to spin‐up. We found that the source recently entered into a new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 32 publications
3
29
2
Order By: Relevance
“…The column density fit in Fig. 6 implies an interstellar column density towards 4U 1907+09 of N ism H ∼4.8 × 10 22 cm −2 , which is slightly higher than literature values (Inam et al 1997; Roberts et al 2001). The error bars in the derived N asm H are considerably large (see Fig.…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The column density fit in Fig. 6 implies an interstellar column density towards 4U 1907+09 of N ism H ∼4.8 × 10 22 cm −2 , which is slightly higher than literature values (Inam et al 1997; Roberts et al 2001). The error bars in the derived N asm H are considerably large (see Fig.…”
Section: Resultscontrasting
confidence: 49%
“…The column density was extracted from spectral fits of 4U 1907+09 by Inam, Sahiner & Baykal (1997), who analysed the RXTE /PCA observations from 2007 and 2008. Data from PCA observations come from ∼2‐ks time intervals (Inam et al 1997); thus, no PCA observation covered a full orbital period. For this work, we chose to study the column density in 4U 1907+09 over the same time period as used in the flux analysis.…”
Section: Rxte/asm Observationsmentioning
confidence: 99%
“…The exact location of 4U 1538−522 relative to L coul varies depending on which mass is used: with the very low-mass elliptical result, the measured Luminosities and values for E cyc from other works are included, along with 90% confidence intervals. Linear fits to the data are also overplotted; due to the systematic differences between Gaussian-and Lorentzian-shaped models for the cyclotron lines, there are two curves for each source: the solid includes only sources that used Gaussian-profile models for the CRSFs, while the dotted line includes Lorentzian-modeled lines (those of Mihara et al 1998;Clark et al 1990;Rodes-Roca et al 2009;Makishima et al 1999;and Inam et al 2009) shifted upward by 1.75 keV.…”
Section: Cyclotron Line Variabilitymentioning
confidence: 99%
“…For ∼15 yr following the identification of the source as a pulsar by Makishima et al (1984), the pulse period increased steadily from 437.4 s in 1984 (Makishima et al 1984) to ∼441 s in 1998, when the spin-down trend began to slow, leading to a torque reversal in 2005 (Fritz et al 2006). This was followed relatively quickly by another reversal in mid-2007 (Inam et al 2009;Şahiner et al 2011) and the source began following approximately the same spin-down trend as it had between 1987 and 1998, a trend that thus far shows no sign of changing. The initial determination of the ∼8.4 day orbital period showed flaring twice per orbit, suggesting the source was in orbit around a Be-type star (Marshall & Ricketts 1980), although subsequent optical observations indicated that the companion was more likely a supergiant (van Kerkwijk et al 1989).…”
Section: Introductionmentioning
confidence: 96%
“…This means that there should be a direct relation between the X-ray pulsational period and the parameters determining r mag [34][35][36][37]. Dramatic spin-up episodes are seen, for example, during giant outbursts of Be X-ray binaries [3,[38][39][40], while many sources show extended spin up/spin down phases indicating that they are close to equilibrium [18,41,42]. These observations allow, in principle, an independent check of magnetic fields obtained from cyclotron lines (see Sect.…”
Section: The Magnetosphere and The Accretion Flowmentioning
confidence: 99%